DFT charge transfer of hybrid molecular ferrocene/Si structures. (2nd April 2015) - Calborean, Adrian; Buimaga-Iarinca, Luiza; Graur, Florin
Abstract: The electrochemical behavior and electronic properties of redox-active ferrocenes grafted onto semiconductor Si(100) substrate were investigated theoretically by first-principles calculations. Organic molecules were attached via the formation of Si-C covalent bonds through two different linkers: vinyl (direct grafting), and N3 (CH2 )11 (indirect grafting). Redox energies and the electronic properties relating to different spacers in hybrid ferrocene Fc/Si and ferrocenium Fc + /Si structures were theoretically extracted and compared with experimental cyclic voltametry data. Electronic charge transfers are discussed through the alignment positions of the frontier orbitals of the molecule with respect to the Si substrate gap. Periodic boundary conditions were used to investigate the Si(100) as a slab surface and hybrid Fc/Si structures. The resulting projected density of states (PDOS) were compared with molecular results and discussed in the light of experimental data.